LEVERAGING ONLINE GAMES FOR ELT: A SYSTEMATIC REVIEW - Risya Kamila; Eti Nurcholisah; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The use of online games in English Language Teaching (ELT) has gained attention for its potential to enhance student engagement and learning outcomes. This study systematically reviews existing literature on the effectiveness of online games in improving vocabulary, grammar, reading, speaking, listening, and learning motivation while identifying key success factors. Following the PRISMA guidelines, 30 studies published between 2020 and 2025 from Google Scholar, PubMed, and Mendeley were analyzed. The findings show that online games create an immersive and interactive learning environment, increasing motivation and facilitating contextual language acquisition. Gamification elements such as points, leaderboards, real-time feedback, and adaptive challenges improve engagement and retention. However, challenges such as limited technological access, insufficient teacher training, and curriculum integration issues hinder implementation. The study concludes that while online games offer significant benefits for ELT, their effectiveness depends on strategic integration and teacher support. Future research should explore best practices for combining online games with traditional teaching methods to optimize learning outcomes.